2014
DOI: 10.3892/ol.2014.2421
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiotherapy to stabilize a tumor embolus in clear cell renal cell carcinoma: A case report

Abstract: Superior vena cava (SVC) syndrome results from clear cell renal cell carcinoma and is a challenge in clinical practice due to its pathological complexity and a lack of research data. The current study presents a 49-year-old female with symptoms of exertional dyspnea and increased fatigue, which had persisted for 15 months, as well as bilateral edema in the lower limbs for two days. A transesophageal echocardiogram demonstrated a right atrial mass originating from the inferior vena cava (IVC; size, 14×8 cm) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Renal cell carcinoma has been considered a radio-resistant malignancy [18,[20][21][22]. Indeed, conventional radiotherapy (2 Gy per fraction) causes only a limited cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Renal cell carcinoma has been considered a radio-resistant malignancy [18,[20][21][22]. Indeed, conventional radiotherapy (2 Gy per fraction) causes only a limited cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…There have been only two reports of radiotherapy for IVC tumor thrombosis of RCC. One is a case report of intensity-modulated radiotherapy (56 Gy/24 fractions of one fraction per day) that stabilized a tumor embolus in clear cell RCC [7]. Another is the only existing report of SRT for IVC tumor thrombus of RCC by Hannan et al, which showed only partial remission at two years follow-up and 18-month survival [8].…”
Section: Discussionmentioning
confidence: 99%
“…This may include a combination of surgery, chemotherapy, and radiation. Interventional approaches include placement of an intravascular stent or surgical bypass grafting [ 5 ]. The patient was noted to have significant improvement in her lower extremity edema after initiation of capecitabine and oxaliplatin, likely resulting in reduction in the size of the metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…An underlying cancer is the cause of more than 90% of cases of the SVC syndrome. Other cancers associated with SVC syndrome include thymoma, mesothelioma, lymphoma, and germ cell tumors [ 5 ]. However, the clinical presentation of these malignancies does not include vena cava compression in most cases.…”
Section: Introductionmentioning
confidence: 99%